Evidence that ebolaviruses and cuevaviruses have been diverging from marburgviruses since the Miocene - Taylor, Derek J. (PeerJ Inc., 2014)
An understanding of the timescale of evolution is critical for comparative virology but remains elusive for many RNA viruses. Age estimates based on mutation rates can severely underestimate divergences for ancient viral genes that are evolving under strong purifying selection. Paleoviral dating, however, can provide minimum age estimates for ancient divergence, but few orthologous paleoviruses are known within clades of extant viruses. For example, ebolaviruses and marburgviruses are well-studied mammalian pathogens, but their comparative biology is difficult to interpret because the existing estimates of divergence are controversial. Here we provide evidence that paleoviral elements of two genes (ebolavirus-like VP35 and NP) in cricetid rodent genomes originated after the divergence of ebolaviruses and cuevaviruses from marburgviruses. We provide evidence of orthology by identifying common paleoviral insertion sites among the rodent genomes. Our findings indicate that ebolaviruses and cuevaviruses have been diverging from marburgviruses since the early Miocene.